(untitled) (Journal of the College of Basic Education, 2023)
Acute leukemias are characterized by the elonogenic proliferation of haemopoietic progenitor cells arrested in maturation. Clinical manifestations are related to the infiltration of the bone marrow and other tissues by the leukemic blasts. Peripheral blood mononuclear cell (PBMC) from luekemic patients (29)ANLL,(36)ALL and from normal donors(55)were typed for HLA- DP specificities using microlymphocytotoxicity assay. Results showed frequencies of DPw alleles in ANLL patients were not significantly different from controls ,exept that in DPw1 was absent .In contrast ,in ALL,frequencies of DPw2 and DPw5 were significantly increased (p<0.05, relative risk (RR) = 1.95 and p<0.01, RR=4.27, respectively. These results ,therefore ,demonstrate both positive negative associations between major histocompatibility complex (MHC) gene products which are in only very weak linkage with the rest of HLA ,and ALL,ANLL patients.The HLD-DP region could thus contain long sought – after genes influencing susceptibility and resistance to leukeemogenesis.